Developing Graduate Students’ Self-Efficacy with Learner-Centred Lecturing - Troop, Meagan A. C.; Wallar, Lauren E.; Aspenlieder, Erin (Canadian Journal of Higher Education, 2015)
This paper presents the findings of a mixed-method case study conducted at the University of Guelph on the relationship between practice lecturing and graduate student self-efficacy. Building on the work of Boman (2013), and using surveys and individual interviews, we measured and characterized the perceived changes in graduate students’ self-efficacy in learner-centred lecturing. Our research question was: In what ways, if any, does microteaching contribute to participants’ perceived self-efficacy in learner-centred lecturing? Our results and discussion reveal that practice increases self-efficacy with respect to the design, facilitation, and assessment of learner-centred lectures, and is a vital component to graduate student teaching development programming.